Nutrition status of elite Jiu-Jitsu athletes during training season - Paiyarat, K.; Techakriengkrai, T.; Jamphon, A.; Penglee, N.; Polyai, N.; Techakriengkrai, W. (Scientific Journal of Sport and Performance, 2024)
Optimizing high-intensity Jiu-Jitsu requires careful nutritional consideration, impacting body composition and performance. Balancing dietary intake with expenditure enhances athlete performance. This study, conducted with ten healthy Jiu-Jitsu athletes from the Jiu-Jitsu Association of Thailand, scrutinized their dietary intake compared to recommendations and its correlation with body composition to enhance performance and training adaptations. Participants completed three days of 24-hour dietary recalls. body composition was assessed using bioelectrical impedance analysis. Across both genders, total energy intake is inadequate, with carbohydrate consumption falling significantly below the recommended levels (p < .05). Female athletes showed significant positive correlations between dietary intake and body composition, notably with protein intake and skeletal muscle mass percentage and the skeletal muscle mass index (r = .895, and .963, respectively, p < .05). Conversely, male athletes displayed no significant correlations, but a broader analysis across genders revealed a strong positive correlation between protein consumption and muscle mass (r = .685, p < .05). The study highlights inadequate dietary intake, particularly in carbohydrates, among Jiu-Jitsu athletes during training, potentially compromising competition performance due to insufficient energy sources. Addressing these nutritional deficiencies is crucial to optimizing performance and body composition, emphasizing the need for dietary practice improvements among Jiu-Jitsu athletes.